'Strengthening the fungal cell wall through chitin–glucan cross‐links: effects on morphogenesis and cell integrity'. (16th June 2016) - Arroyo, Javier; Farkaš, Vladimír; Sanz, Ana Belén; Cabib, Enrico
Summary: The cross‐linking of polysaccharides to assemble new cell wall in fungi requires transglycosylation mechanisms by which preexisting glycosidic linkages are broken and new linkages are created between the polysaccharides. The molecular mechanisms for these processes, which are essential for fungal cell biology, are only now beginning to be elucidated. Recent development of in vivo and in vitro biochemical approaches has allowed characterization of important aspects about the formation of chitin–glucan covalent cell wall cross‐links by cell wall transglycosylases of the CRH family and their biological function. Covalent linkages between chitin and glucan mediated by Crh proteins control morphogenesis and also play important roles in the remodeling of the fungal cell wall as part of the compensatory responses necessary to counterbalance cell wall stress. These enzymes are encoded by multigene families of redundant proteins very well conserved in fungal genomes but absent in mammalian cells. Understanding the molecular basis of fungal adaptation to cell wall stress through these and other cell wall remodeling enzymatic activities offers an opportunity to explore novel antifungal treatments and to identify potential fungal virulence factors.